Advances in Polymeric Materials for Electromechanical Devices. Issue 1 (24th October 2018) - White, B. Tyler; Long, Timothy E.
Abstract: Electroactive polymers (EAP) provide lightweight and cost‐effective materials that enable the next generation of electromechanical devices. Commercial polymers have historically dominated research in EAP devices due to their availability. However, several drawbacks of these materials have limited their commercial applications, necessitating new materials for the commercial success of future EAP devices. This review highlights recent advances in novel EAPs for ionic polymer‐metal composites (IPMC) and dielectric elastomer actuators (DEA). Ion‐containing block copolymers and charged segmented condensation polymers demonstrate suitable electromechanical properties competitive with Nafion‐based IPMCs. In addition, swelling ionic polymer membranes with free ionic liquid enhances ionic conductivity and promotes electromechanical actuation. Synthetic approaches to increasing permittivity in dielectric elastomers are also explored as a method of producing more efficient DEAs. Incorporating polar functional groups into siloxane and acrylic elastomers through grafting or blending provides high‐dielectric elastomers for use in DEAs with low driving voltages. Abstract : Electroactive polymers show promise for use in lightweight, flexible devices such as sensors, artificial muscles, and soft robotics. This review summarizes recent synthetic polymers used in electromechanical transducers with an emphasis on the synthetic design and physical properties required for high performance.